Peningkatan Keterampilan Menulis Teks Prosedur Melalui Penggunaan Media Video - Juni Sahla Nasution; Dinah Nadhifah; Wahyu Azhari; Abdal Rizky Munthe (Universitas Maritim AMNI Semarang, 2024)
The aim of this research is to determine the improvement of procedure text writing skills through the use of video media. The research method used is a literature review which collects descriptive information and data regarding improving writing skills using video media. The research results show that using video media can improve students' writing skills because videos can display real information in an interesting and not boring presentation so that students' interest in learning increases and helps expand vocabulary for writing procedural texts.